Pengaruh Online Customer Review dan Brand Image terhadap Purchase Decision Produk Scarlett Whitening di Tiktok Shop (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Program Studi Manajemen) - Sanida, Nurissanida; Amellia, Monica; Ali Alam, Iskandar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), 2024)
The aim of this study is to determine how abstrac Online Customer Reviews and Brand Image affect the Purchase Decision of Scarlett Whitening products on Tiktok Shop. The research design was carried out using quantitative methods. The number of research samples consisted of 70 respondents, which was obtained by applying the Nonprobability Sampling method through a purposive sampling approach. Data was obtained through questionnaires. The techniques applied in data analysis are classical assumption test, multiple linear regression, t-test, F test, and determination coefficient (R2). The results of this study indicate that online customer reviews do not have a significant influence on the purchase decision of Scarlett Whitening products and Brand Image has a significant influence on the purchase decision of Scarlett Whitening products. In addition, Online Customer Reviews and Brand Image have a simultaneous influence on Scarlett Whitening's product purchase decisions.